Recalcitrant erythrodermic ichthyosis with atopic dermatitis successfully treated with Dupilumab in combination with Guselkumab - M. Steinhoff; F. Al‐Marri; R. Al Chalabi; U. Gieler; J. Buddenkotte (Wiley, 2022)
Abstract Background Autosomal recessive congenital ichthyosis refers to a group of rare inherited disorders of keratinization and defective epidermal barrier resulting in varying clinical presentations and severities ranging from harlequin ichthyosis to congenital ichthyosiform erythroderma (CIE). Secondary atopic dermatitis (AD) can aggravate the disease state for CIE patients leading to recalcitrant CIE/AD with potentially unfavourable side effects and low tolerability. Aims Here, we report about a 38‐year‐old male patient with severe CIE as well as AD over the last 30 years. Materials and Methods The patients suffered from severe inflammation, pruritus and recurrent infections for decades without disease control and intolerable adverse events of previous therapies. Results Dupilumab (targeting IL‐4Ra, 300 mg q2w) partially controlled pruritus, but only the combination of Dupilumab with Guselkumab (anti‐IL23p19) controlled both CIE and AD with markedly reduced inflammation, itch and recurrent infections. Guselkumab alone was not sufficient to treat the severe CIE/AD. Discussion Further studies are required to assess the efficacy and safety of targeted therapies like Dupilumab/Guselkumab combination therapy in severe CIE/AD.